2013
DOI: 10.1002/pca.2466
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Small Combinatorial Libraries of Natural Products: Identification and Quantification of New Long‐chain 3‐Methyl‐2‐alkanones from the Root Essential Oil of Inula helenium L. (Asteraceae)

Abstract: The small combinatorial library approach enabled the first unequivocal identification of long-chain 3-methyl-2-alkanones as plant secondary metabolites, and, also, allowed determination of not only a single compound and biological properties, but those of a group of structurally related compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Although meager research has been conducted in IH, the findings presented here are in alignment with existing researchers who have reported its capacity to attenuate iNOS/NO2-, COX-2/PGE2, HMGB1 release and NF-κB in LPS-activated RAW 264.7 cells or phorbol activated T cells [45–48]. Interestingly, although we did not find IH to have significant antimicrobial effects on E.coli 0157:H7 (1x10 6 CFU/mL) at the low concentrations criteria used in this study, others have reported its capacity to destroy invasive pathogens such as Staphylococcus aureus /methicillin-resistant (MRSA) gram-positive bacteria, yeasts parasites and Mycobacterium tuberculosis [42, 4953]. These studies suggest IH as being somewhat promising for attenuating inflammation arising from diverse infective or inflammatory insults.…”
Section: Discussionmentioning
confidence: 55%
“…Although meager research has been conducted in IH, the findings presented here are in alignment with existing researchers who have reported its capacity to attenuate iNOS/NO2-, COX-2/PGE2, HMGB1 release and NF-κB in LPS-activated RAW 264.7 cells or phorbol activated T cells [45–48]. Interestingly, although we did not find IH to have significant antimicrobial effects on E.coli 0157:H7 (1x10 6 CFU/mL) at the low concentrations criteria used in this study, others have reported its capacity to destroy invasive pathogens such as Staphylococcus aureus /methicillin-resistant (MRSA) gram-positive bacteria, yeasts parasites and Mycobacterium tuberculosis [42, 4953]. These studies suggest IH as being somewhat promising for attenuating inflammation arising from diverse infective or inflammatory insults.…”
Section: Discussionmentioning
confidence: 55%
“…SLA enables a simultaneous identification of not only specific, new compounds, but of a series of its homologs/analogs (Figure ). This approach was recently successfully applied in the analysis of different essential oil samples …”
Section: Introductionmentioning
confidence: 99%
“…Although previous applications of SLA were mainly targeted ones (libraries of compounds were designed to resolve problems related to a single EO sample), the possible benefits of a more general employment of SLA in EO chemistry was already recognized . In this more universal approach, chemical profiles of previously studied essential oils are used as ‘sources of the likely SL‐parent‐structures’ (SL‐synthetic library), Figure , route c, step 1.…”
Section: Introductionmentioning
confidence: 99%
“…The resolution of accidently overlapped signals from two or more different molecules could be a plausible outcome of a gradual addition of a LSR directly to the mixture since a distinct conduct of these signals is expected due to molecular differences (differing spatial relationship with the LSR complexing functional group and its identity), competitive complexation (differing stabilities of the LSR complexes of different mixture constituents) and shiing of the complexation equilibrium by different amounts of the individual constituents. 19,20 The identity of the 3-methyl-2-alkanones was conrmed by a synthetic approach based on the creation of a combinatorial library of such compounds since the amount and complexity of the fraction did not permit further chromatographic separation. [15][16][17] Also, the presence of LSR, that are paramagnetic in nature, should result in the increased 13 C NMR sensitivity and shorten the time needed to acquire good quality spectra even for samples available in low amount.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Also, the presence of LSR, that are paramagnetic in nature, should result in the increased 13 C NMR sensitivity and shorten the time needed to acquire good quality spectra even for samples available in low amount. 20 In order to identify this sesquiterpene aldehyde, a larger quantity of the essential oil was fractionated by chromatography on SiO 2 . 1 The original TIC chromatogram of a GC-MS run of a fraction (5% diethyl ether in hexane) of I. helenium root essential oil showing peaks with retention indices (blue colored) corresponding to a series of 3-methyl-2-alkanones and an unidentified sesquiterpene aldehyde (green colored) and the mass spectrum of the aldehyde.…”
Section: Introductionmentioning
confidence: 99%